KARAKTERISTIK MUTU YOGHURT BUAH NAGA MERAH (HYLOCEREUS POLYRHIZUS) SELAMA PENYIMPANAN - Haganta Bangun; Usman Pato; Emma Riftyan (Fakultas Pertanian Universitas Riau, 2025)
Yogurt is a beverage product processed through milk fermentation using Lactobacillus bulgaricus and Streptoccocus thermophilus. To add flavor, color, and aroma so as to improve the oraganoleptic properties of yogurt, it is necessary to add fruit in the manufacturing process such as dragon fruit. The use of red dragon fruit puree in yogurt is expected to increase the shelf life of yogurt, improve organoleptic, and increase the nutritional value of yogurt, as well the antioxidants content that function to prevent or delay several types of cell damage due to the oxidation. This study aimed to determine the quality characteristics of red dragon fruit yogurt during storage. The research was carried out using a completely randomized design with four treatments. The treatments in the study included storage times of 0, 7, 14, and 21 days at cold temperatures (4°C) which were repeated four times to obtain 16 experimental units. The data obtained were analyzed statistically using the ANOVA test. If the calculated F value is greater than or equal to the F table, then it is continued with Duncan's New Multiple Range Test (DNMRT) at the 5% level. The results of the analysis of variance showed that the storage times of red dragon fruit yogurt had a significant effect on the degree of the total lastic acid bacteria, total titratable acid, pH and viscosity. The results showed that the strorage period of red dragon fruit yoghurt had no significant effect on antioxidant activity as well as descriptive sensory assessment. The selected treatment was, P3 (14 days) red dragon fruit yogurt with, total LAB of 8.91 log CFU/ml, pH of 4.76, total titrated acid of 0.369%, viscosity of 726.82cP, and antioxidant of 10.52 ppm. The yogurt in P3 (14 days) treatment tasted sour, was red, smelled like dragon fruit, was a little thick.